Political participation and voluntary associations : A hypergraph case study. - Amina Azaiez; Robin Salot (PLoS ONE)
Civic organizations, ranging from interest groups to voluntary associations, significantly influence policy formation in representative democracies. This work presents a local case study that examines the relationship between voluntary associations and local political institutions in a village with nearly two thousand residents. Traditionally, sociologists' approaches have focused on individual characteristics such as age, gender, or socio-professional status. In this study, we analyze social interactions between members of organizations modeled through a hypergraph. Specifically, we model interactions as hyperedges that correspond to activities proposed by organizations and involve the individuals who participate in those activities. Our analysis reveals a community-based structure, where members of similar types of organizations tend to interact more frequently. To quantify 'political participation,' we introduce an interaction-based measure that extends degree centrality. We also introduce the 'diversity coefficient' as an extension of degree centrality to capture an individual's ability to participate in activities composed of members from different communities. Among other centrality measures, we find that the diversity coefficient is the most significant factor in explaining political participation among members of associations.